Pengaruh Citra Merek, Iklan, Dan Kualitas Produk Terhadap Minat Beli Konsumen Pada Produk Kopi Kapal Api Di Surabaya - Alfiah Nofiana; Aridha Prassetya; Achmad Daengs GS; Mahjudin Mahjudin; Diana Zuhroh (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
Producers of packaged instant coffee have to compete fiercely to get consumers' attention, because the many types of packaged instant coffee on offer make consumers increasingly free to make their choices. Kapal Api Coffee producers need to evaluate marketing policies in the form of brand image, advertising and product quality and their influence on consumer demand to buy, so that they are expected to be able to innovate to increase their sales. This research aims to find out whether there is an influence on brand image, advertising and product quality on consumer buying interest in Kapal Api Coffee products in Surabaya. This research approach uses quantitative research. The data used are the answers of respondents from the results of distributing questionnaires. Data analysis techniques using multiple linear regression analysis, F test, and t test. Based on the research results, it is known that brand image, advertising and product quality simultaneously influence consumer buying interest in Kapal Api Coffee products, because the F test results show the calculated F value is greater than F table, namely 34.040 > 2.699. Brand image partially influences consumer buying interest in Kapal Api Coffee products, this is proven by the t test which shows the calculated t value is greater than the t table, namely 4.569 > 1.985. Advertising partially influences consumer buying interest in Kapal Api Coffee products, this is proven by the t test which shows the calculated t value is greater than the t table, namely 2.190 > 1.985. Product quality partially influences consumer buying interest in Kapal Api Coffee products, this is proven by the t test which shows the calculated t value is greater than the t table, namely 3.531 > 1.985. Based on the results of the study it is also known that brand image (X1) has a dominant effect on purchase intention. This is proven by the t test where the calculated t value of brand image (X1) is greater than the calculated t value of the advertising variables (X2) and product quality (X3), namely 4.569.